2020
DOI: 10.1590/1414-431x20198616
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-383 suppresses oxidative stress and improves endothelial function by increasing sirtuin 1

Abstract: Previous research has shown that suppression of miR-383 can prevent inflammation of the endothelium, as well as postpone the development of atherosclerosis. However, the role of miR-383 in endothelial cell apoptosis in diabetes remains unclear. The aim of this study was to investigate the function of miR-383 in high glucose-induced apoptosis and oxidative stress in endothelial cells. A series of experiments involving qualitative polymerase chain reaction, cell transfection, luciferase assay, assessment of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…MiR-92a inhibition reduces oxidative stress and improves endothelial function by upregulating the expression of HO-1 [ 95 ]. Inhibition of miR-383 reduced ROS by upregulating SIRT1, increasing SOD1/CAT levels, and enhancing endothelial cell activity [ 96 ].…”
Section: Mechanisms Of Ros-induced Endothelial Dysfunction In Diabeti...mentioning
confidence: 99%
“…MiR-92a inhibition reduces oxidative stress and improves endothelial function by upregulating the expression of HO-1 [ 95 ]. Inhibition of miR-383 reduced ROS by upregulating SIRT1, increasing SOD1/CAT levels, and enhancing endothelial cell activity [ 96 ].…”
Section: Mechanisms Of Ros-induced Endothelial Dysfunction In Diabeti...mentioning
confidence: 99%
“…Hu found that miR-383 was capable of inducing ROS generation and promote cell apoptosis [23]. Relevant studies have shown that miR-383 is associated with reproduction-related miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the role of miRNA in biological physiological, and pathological processes has gradually become clear, especially in the field of chronic diseases such as diabetes. Studies have found that miRNA-34a, miRNA-24, miRNA-181c, miRNA-29b, miRNA-200a, miRNA-383, and other miRNAs play a role in inflammation ( Li, Kim et al, 2016 ; Lo, Yang et al, 2018 ; Shen, Li et al, 2018 ; Cheng, Chen et al, 2019 ; Zhang, Cai et al, 2019 ; Hu, Gong et al, 2020 ), thus participating in the occurrence of endothelial dysfunction in diabetes. To study the exact mechanism of vaccarin in regulating HDAC1, databases were used to screen the possible miRNA targets ( Figure 6A ).…”
Section: Discussionmentioning
confidence: 99%